DEVELOPMENT, OPTIMIZATION AND EVALUATION OF PULSATILE DRUG DELIVERY CAPSULES LOADED WITH CARVEDILOL BY APPLYING QUALITY BY DESIGN - KUMAR A., BHARATH; KUMAR GAUTAM, GIRENDRA; B., SYED SALMAN (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this research is to find the best way for designing carvedilol pulsatile drug delivery system capsules. Methods: The research paves the way to improve the method of preparing carvedilol pulsatile drug delivery by adjusting critical material attributes (CMA) such as coating polymer concentration, critical process parameters (CPP) such as inlet temperature and atomizing air pressure, and their impact on critical quality attributes (CQA) like particle size (PS in nm), entrapment efficiency in percentage (% EE) and amount of drug delivered in percent (%ADR) at 12 h in the carvedilol pulsatile pellets filled capsules by applying the Box-Behnken design. By varying the polymer concentration and process parameters, nearly 15 formulations were created. Results: Based on the influence of CMA, CPP on CQA, the formulation CP13 was determined to be the most optimized formulation among the 15 formulations. The optimized levels of CMA were found to be-1 level of coating polymer concentration and CPP was found to be-1 level of inlet temperature, 0 level of atomizing air pressure and it optimized CQA like PS was found to be 1017.5±8.4 nm, % EE was found to be 96.8±2.8 %, % ADR at 12 h was found to be 88.4±3.4 %. Carvedilol Pulsatile drug delivery system was designed by using optimized fluidized bed coater in order to decrease the usage of attributes, decrease the productivity cost and enhance the usage of specific attributes at fixed concentration for further manufacturing scale. Conclusion: By the current results it was concluded that the optimized CMA and CPP that shown in the results are the suitable attributes for the best formulation of carvedilol pulsatile drug delivery system capsules.